Hydrothermal Liquefaction of Agricultural Residues for Renewable Bio-Crude Production: Energy Yield and Emission Reduction Potential - Thomas Schmidt; Fatemeh Rezaei; Zhang Wei; Ahmad Fikri bin Abdullah; Nguyen Van Hung (Gio Vani Publisher, 2026)
The escalating global energy demand, coupled with the imperative to reduce greenhouse gas emissions, necessitates the development of sustainable alternatives to fossil fuels. This study investigates the Hydrothermal Liquefaction (HTL) of abundant agricultural residues—sugarcane bagasse, wheat straw, and rice husk—for the production of renewable bio-crude oil. Experiments were conducted in a batch reactor at temperatures ranging from 280–320°C to optimize the yield and quality of bio-crude. The results showed that a reaction temperature of 300°C yielded maximum bio-crude outputs of 38.2 wt%, 42.5 wt%, and 35.1 wt% (dry ash-free basis) for bagasse, wheat straw, and rice husk, respectively, with corresponding energy recoveries of up to 78.5%. The bio-crude exhibited improved fuel properties, with higher heating values between 30–34 MJ/kg. A comprehensive life cycle assessment (LCA) revealed that the integrated HTL system, when accounting for avoided fossil fuel use and prevention of open-field burning, achieves net-negative greenhouse gas emissions, ranging from -32.1 to -47.4 g CO₂-eq per MJ of bio-crude. The findings confirm that HTL of agricultural waste is a technically feasible and environmentally strategic pathway for producing low-carbon liquid biofuels, directly contributing to waste valorization, energy security, and climate change mitigation by phasing out fossil-derived fuels.